Tortilla de Pastilla (UMA Editorial (Universidad de Málaga), 2025)
The following is a project undertaken by the Department of Pharmacology at the Faculty of Medicine, University of Malaga. In collaboration with nursing students, for the elaboration of a completely original text and visual material, intended for Health Sciences students in those subjects that deal with the discipline related to the department. These notes have been prepared with a didactic and student support intention, as well as scientific dissemination, following the directive of teachers experienced in the subject and recognized, this material has been reviewed and oriented on the basis of pharmacology teaching. Below, we present the following index detailing the topics that make up the work and the resources it offers.